Factors affecting commencement and cessation of betel quid chewing behaviour in Malaysian adults. - Ghani, W.M.; Razak, I.A.; Yang, Yi-H.; Talib, N.A.; Ikeda, N.; Axell, T.; Gupta, P.C.; Handa, Y.; Abdullah, N.; Zain, R.B. (BioMed Central, 2011)
Factors that influence the development and cessation of this behaviour are gender, age, ethnicity, and also history of smoking habit while frequency and type of quid chewed are important factors for cessation of this habit.